What do the Public Understand About Intimate Partner Violence in the Context of Military Veteran Status and PTSD? - Mackinnon, Jessica; Paskell, Rachel; Hamilton-Giachritsis, Catherine (Psychological reports, 2025)
Intimate Partner Violence (IPV) represents a significant public and social health concern and may present particular complexities in military veteran relationships which are subject to unique stressors including separations, transition to civilian life and increased risk of Post-Traumatic Stress Disorder (PTSD). Public understanding is vital in terms of ensuring access to services and appropriate intervention. However, little is known about the public perception of IPV in this context. This study sought to assess how public recognition and discourse is affected by military veteran status and a diagnosis of PTSD. Community participants (N = 269) were randomly allocated to one of four conditions and presented with a story containing IPV in which the profession (military veteran/civilian worker) and diagnostic status (PTSD/No PTSD) were manipulated. All participants rated the extent to which they felt the story contained IPV; additionally, half (n = 123) took part in a story completion task designed to elicit qualitative data with regards to public discourse. The mean scores in all conditions were weighted towards IPV recognition. Results indicated a small interaction between job role and PTSD (F[1265] = 7.888, p < 0.01, partial n2 = 0.029) meaning that the public are more likely to recognise IPV when it is perpetrated by a military veteran than a civilian with PTSD. Diagnostic status made no difference to recognising abuse perpetrated by a military veteran. However, the fit of the model was weak (r2 = .040) meaning that the large majority of variance was due to factors not accounted for. Qualitative findings indicated that in a military population trauma may be assumed even where not indicated and the public appear less likely to consider current stressors or acknowledge that PTSD cannot justify abuse. Victims of IPV in military relationships may therefore be particularly vulnerable to discourses that prioritise the victim status of the perpetrator.